Formation of Brominated Disinfection Byproducts from Natural Organic Matter Isolates and Model Compounds in a Sulfate Radical-Based Oxidation Process - Wang, Y.; Roux, J.L.; Zhang, T.; Croue, Jean-Philippe (American Chemical Society, 2014)
A sulfate radical-based advanced oxidation process (SR-AOP) has received increasing application interest for the removal of water/ wastewater contaminants. However, limited knowledge is available on its side effects. This study investigated the side effects in terms of the production of total organic bromine (TOBr) and brominated disinfection byproducts (Br-DBPs) in the presence of bromide ion and organic matter in water. Sulfate radical was generated by heterogeneous catalytic activation of peroxymonosulfate. Isolated natural organic matter (NOM) fractions as well as low molecular weight (LMW) compounds were used as model organic matter. Considerable amounts of TOBr were produced by SR-AOP, where bromoform (TBM) and dibromoacetic acid (DBAA) were identified as dominant Br-DBPs. In general, SR-AOP favored the formation of DBAA, which is quite distinct from bromination with HOBr/OBr- (more TBM production). SR-AOP experimental results indicate that bromine incorporation is distributed among both hydrophobic and hydrophilic NOM fractions. Studies on model precursors reveal that LMW acids are reactive TBM precursors (citric acid > succinic acid > pyruvic acid > maleic acid). High DBAA formation from citric acid, aspartic acid, and asparagine was observed; meanwhile aspartic acid and asparagine were the major precursors of dibromoacetonitrile and dibromoacetamide, respectively.